Peranan Teknologi Pendidikan dalam Peningkatan Mutu Pendidikan - Suhada Suhada (Hikmah: Journal of Islamic Studies, 2017)
Problems related to the quality of education have long become a concern of all educational stakeholders. The stakeholders of the quality of education have thought about how to improve the quality of education in various ways. One of the efforts is by using educational technology. The educational technology can help to solve learning problems. Systemic process can be understood in twosenses:irregularorregularthatreferstoasystem.Asaregular system, the educational technology is the process that is preceded by studying the needs, formulating the objectives, identifying the possible achievement of goals, determining the possibility of selection criteria, selecting the best possibility, developing and testing the chosen possibility, carrying out developmentresults, and evaluating the overall activities and results. As a product, the educationaltechnologycanbeunderstoodastheprocesses,which arecomplexandintegratedthatinvolvepeople,procedures,ideas, tools, and organizations to analyze problems, find ways to solve problems,implement, assess, andmanagethesolutionsthat cover all aspects of human learning. The educational technology was born from the problems in education. It not only helps to solve the problems of learning in the school, but in the whole contexts of people’s lives by developing and/or using a variety of sources. In the context of school, the technology of education evolves from what was originally known as didactic and methodical. However, because learning is not only in the context of school, but in the whole contexts of the community, the educational technology operates in which learning is required, either by individuals, groups or organizations. Keywords : education, technology of education, and the quality of education. Permasalahan terkait mutu pendidikan telah sejak lama menjadi konsen bersama seluruh stake holder pendidikan. Seluruh pihak yang berkepentingan terhadap mutu pendidikan memikirkan mengenai bagaimana meningkatkan mutu pendidikan dengan berbagai cara. Salah satu upaya yang ditempuh adalahdengan menggunakan teknologi pendidikan. Teknologi pendidikan dapat membantu memecahkan masalahmasalah pembelajaran. Proses sistemik dapat dipahami dalam dua pengertian; beraturan atau mengacu pada suatu sistem. Sebagai sistem yang beraturan, teknologi pendidikan adalah proses yang didahului dengan telaah kebutuhan, perumusan tujuan, identifikasi kemungkinan pencapaian tujuan, penentuan kriteria pemilihan kemungkinan, memilih kemungkinan terbaik, mengembangkan dan mengujicoba kemungkinan yang dipilih, melaksanakan hasil pengembangan, dan mengevaluasi keseluruhan kegiatan maupun hasilnya. Sebagai produk, teknologi pendidikan bisa dipahami sebagai perangkat proses, yang bersifat kompleks dan terpadu melibatkan orang, prosedur, ide, peralatan, dan organisasi untuk menganalisis masalah, mencari jalan untuk mengatasi permasalahan, melaksanakan, menilai, dan mengelola pemecahan masalah tersebut yang mencakup semua aspek belajar manusia. Teknologi pendidikan lahir dari adanya permasalahan dalam pendidikan. Teknologi pendidikan tidak hanya membantu memecahkan masalah belajar dalam konteks sekolah, namun dalam seluruh konteks kehidupan masyarakat, dengan mengembangkan dan/atau menggunakan beraneka sumber. Dalam konteks sekolah teknologi pendidikan berkembang dari apa yang semula dikenal dengan istilah didaktik dan metodik. Namun karena belajar tidak hanya dalam konteks sekolah, tetapi dalam seluruh konteks masyarakat, maka teknologi pendidikan beroperasi di mana belajar itu diperlukan, baik oleh perorangan, kelompok maupun organisasi. Kata Kunci: pendidikan, teknologi pendidikan, mutu pendidikan.